The Caucasus Mineral Waters Region and its contribution to food security - Kaishev , V.G.; Sycheva , O.V. (Journal of the University of Zulia, 2021)
LLC "Agrofirma" Village named after G.V. Kaishev" and LLC "Pyatigorsk Dairy Plant" are a modern agricultural holding, which carries out a full closed cycle - from the production of animal feed and raw milk to a wide range of dairy products. Objective: Analysis of the contribution of the Caucasus Mineral Waters region to food security, by studying the productive efficiency of the agricultural holding LLC "Agrofirma" Village named after G.V. Kaishev" LLC "Pyatigorsk Dairy Plant". Materials and methods. Data of statistical reporting, zootechnical and production accounting, subjected to systematization and critical analysis by the method of scientific knowledge. Results. Production buildings are located on a flat hill, and around the land for growing feed, which allows to provide all livestock with feed of own production. The daily volume of milk supplied for processing to “Pyatigorsk Dairy Plant” LLC is about 40 tons. Milk production is cost effective. In the near future, it is planned to increase the dairy herd from 1200 to 3860 heads and milk production to 200 tons. Conclusion. The key to obtaining high milk productivity and milk quality is optimal conditions for keeping, feeding and milking animals. This is a serious contribution to solving the problem of food security in the KMV region (Kavkazskie Mineralnye Vody).